Transcriptome Sequencing-Based Analysis of Premature Fruiting in Amomum villosum Lour. - Yating Zhu; Shuang Li; Hongyou Zhao; Qianxia Li; Yanfang Wang; Chunyong Yang; Ge Li; Yanqian Wang; Lixia Zhang (Biology)
Amomum villosum Lour., a perennial medicinal plant in the Zingiber genus, usually requires approximately 3–4 years of vegetative growth from seed germination to first fruiting, resulting in high initial investment costs and a prolonged revenue cycle, which pose significant challenges to the industry’s sustainable development. Our research team observed a distinct premature fruiting phenomenon in A. villosum. We investigated the regulatory mechanisms underlying premature fruiting in A. villosum by identifying the key differentially expressed genes (DEGs) and metabolic pathways governing the premature fruiting (Precocious) and typical plants (CK) of the ‘Yunsha No.8’ cultivar. Transcriptomic sequencing (RNA-seq) and bioinformatic analyses were performed using the DNBSEQTM platform. The sequencing generated 29.0 gigabases (Gb) of clean data, and 115,965 unigenes were identified, with an average length of 1368 bp. Based on the sequencing results, 1545 DEGs were identified. Gene ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were annotated for these DEGs. This study identifies phytohormone signaling, carbohydrate and lipid metabolism, and polysaccharide degradation as critical pathways controlling premature fruiting in A. villosum. Six randomly selected DEGs were validated using real-time fluorescence quantitative polymerase chain reaction (RT-qPCR), and the results corroborated the transcriptome data, confirming their reliability. This study lays the foundation for the elucidation of the molecular mechanisms and metabolic pathways driving premature fruiting in A. villosum.